Opening the Doors of a Substance Use Disorder Ward—Benefits and Challenges From a Consumer Perspective - Steinauer, Regine; Krückl, Jana S.; Moeller, Julian; Vogel, Marc; Wiesbeck, Gerhard A.; Walter, Marc; Lang, Undine E.; Huber, Christian G. (Frontiers in Psychiatry, 2020)
Open doors in psychiatry have been a subject of controversy in recent years. While some studies postulate the clinical necessity of closed doors, others challenge the theoretical advantages of this setting, mention numerous drawbacks of closed wards, and focus on the advantages of open-door settings. With regard to patients diagnosed with substance use disorders (SUD), other standards may apply. Very little research has been done on this topic. Some studies adopted a consumer perspective (i.e. asking involved parties about their experience of the door status). To the authors’ knowledge, no study has so far addressed the ideal setting for the treatment of SUD. With our data from the opening of a specialized SUD ward, we take one step to closing this knowledge gap. Applying a qualitative design, we asked patients and health care professionals (HCP) to report changes following the opening of the ward. The results are mainly in line with the literature on the general psychiatric population. The newly introduced open-door setting was mostly perceived as positive, but some disadvantages were mentioned (e.g. less protection of patients, less control over who enters/leaves the ward, the theoretically increased risk of patients absconding). Moreover, HCP (but not patients) mentioned potentially increased substance use on the ward as an additional disadvantage that could arise. Opening a previously closed ward was generally perceived as a positive and progressive decision. These findings support the trend towards an overall open-door policy in psychiatry.